Kadar Zat Besi (Fe) dan Daya Terima Flakes Talas (Colocasia esculenta (L.) Schott) dengan Substitusi Bayam (Amaranth sp.) - Aan Sofyan; Naziela Eldiana Husna AZ (Jurnal Gizi, 2019)
Flakes is a type of practical cereal food product that can be used for breakfast. Flakes product development is needed to improve physical, chemical and nutritional quality characteristics. Taro as a source of local food can be processed for basic ingredients of flakes. The combination of taro and spinach is expected to be an alternative diversification of flakes products that can be a source of Fe and can be accepted by panelists. The purpose of this study is to analyze the levels of Fe in taro flakes products with spinach substitution. The study was conducted by making variations oftaro-based flakes with different percentages of spinach paste substitution, namely: SB1 (100: 0); SB2 (90:10); SB3 (80:20); SB4 (70:30). The results of the analysis of iron flakes content in a row are 20.56; 25.83; 30.77; and 34.25 mg/kg, while the results of the acceptability analysis showed that flakes with spinach substitution of 0% (SB1) was more acceptable both in the aspect of aroma, taste, texture, color, and overall.Keyword: flakes, taro, spinach, iron, acceptability